Growth and andrographolide content of Andrographis paniculata grown on different growing media and media water status - Muslianie Md Isa
Andrographis paniculata (Hempedu bumi) is a medicinal plant that widely distributed in avariety of habitats throughout the world. It has a wide range of medicinal andpharmacological application. This study is aims to investigate the effect of differentgrowing media and media water status on the growth and bioactive compound(andrographolide) content of A: paniculata. An experiment was conducted at thegreenhouse Institute of Sustainable Agrotechnology (INSAT), Universiti Malaysia Perlis(UniMAP) during April 2012 to February 2013. The experiment was laid out in randomizedcomplete block design (RCBD) of two factors consisting of 9 treatments with 3replications. Each replication consisted of 24 plants. Three different growing media wereapplied, namely compost, topsoil and sand. The growing media were combined in differentratios (1:2:3, 2:2:1 and 3:2:1) with three different soil water potential; -20 kPa (high), -60kPa (medium) and -100 kPa (low). Soil water potential in each growing media wasmeasured by gypsum block. The crops were harvested 115 Days after transplanting atmaturity. Analysis of andrographolide content in each treatment was analyzed by usingHigh Performance Liquid Chromatography (HPLC) for each of plant parts (leaves, stemsand roots). Generally, there were significant increases (P <0.05) in plant height, number ofleaves per plant, number of branches per plant, diameter of stem, leaves dry weight, stemdry weight, root dry weight, total dry weight per plant and andrographolide content in eachplant part of plants that had been planted in media mixture contained compost: topsoil: sand(3:2:1) under high soil water potential compared to other treatments. However, the root toshoot ratio of plant that had been planted on the lowest compost ratio under low soil waterpotential produced the highest ratio compared to other treatments. Significant interactioneffects between growing media and soil water potential were observed for all parameters.The study concluded that the application of potting mixture that contained compost, topsoiland sand in a ratio 3:2:1 with well water supplied are recommended for A. paniculatagrown under greenhouse condition.